Kelayakan Media Interaktif Berbasis Nearpod pada Materi Sistem Ekskresi di Kelas XI SMA - Kurnia Ningsih; Ruqiah Ganda Putri Panjaitan; Rofiana Kusuma Pinawadhani (Bioscientist : Jurnal Ilmiah Biologi, 2023)
The rapid development of information technology in the era of globalization has changed the paradigm of society. Global demands for utilizing technology also influence education, which is always aligned as a form of effort to improve the quality of education. Nearpod is a media in the form of a web application that allows students and educators to interact face-to-face or remotely, and is able to provide innovative, interactive and effective learning experiences. The aim of this research is to develop nearpod-based interactive learning media on excretory system material in class XI. The method used is research and development with the ADDIE development model limited to the development stage. Validation was carried out by five validators with three aspects of media assessment, namely language, material and media aspects. The validator's assessment was tested using validity analysis using Aiken and reliability using ICC, and obtained a validity analysis result of 0.92 which was in the very high validity category, and a reliability analysis result of 0.796 which was in the good category, so it can be concluded that nearpod media is valid and feasible used in learning.